Patossistema Colletotrichum spp. x Carya illinoinensis, caracterização e controle - Poletto, Tales (2022)
Pecan (Carya illinoinensis) is an important species cultivated commercially in several countries around the world. More than 100 years ago, North American cultivars were introduced in southern Brazil. Since this introduction, family farmers carry out the cultivation, propagation and selection of these cultivars, as well as plants of seminal origin, based on morpho-agronomic characteristics. This process gave rise to several other genotypes, regionally adapted and with productive potential. In this context, the recent increase in cultivated areas has increased the occurrence of diseases, such as anthracnose, urgently demanding efficient and safe phytosanitary control tools. The aim of this study was to characterize the Colletotrichum spp. x pecan, perform the morphometric, chemical and genetic characterization of pecan genotypes, as well as seek control tools for the disease, through sources of genetic resistance and the selection of biocontrol agents to Colletotrichum spp. For the characterization of the Colletotrichum spp. x pecan, morphological, molecular and pathogenic approaches were used to characterize Colletotrichum species, based on 68 isolates associated with symptomatic fruits, collected in the State of Rio Grande do Sul. The genetic diversity of pecan plants was characterized by morphometric and chemical methods and genetic-molecular analysis based on 60 pecan genotypes. Sensitivity tests were carried out in 18 genotypes, through the inoculation of fruits and leaflets with three species of Colletotrichum, under controlled conditions. Microsatellite molecular markers were used to estimate diversity and compare genotypes according to resistance to Colletotrichum spp. The biocontrol test was performed using six species of the antagonist Trichoderma spp. and five species of the pathogen Colletotrichum spp. The antagonist potential was evaluated by inhibiting the mycelial growth of the pathogens. Six species associated with pecan anthracnose were identified: C. nymphaeae, C. fioriniae, C. gloeosporioides, C. siamense, C. kahawae and C. karstii, which showed different aggressive responses in pecan fruits and leaflets. The genetic diversity of pecan genotypes was moderate to high, which could serve as a source of germplasm for crop improvement. In the sensitivity test, anthracnose manifested itself more severely in the fruits than in the leaflets. Genotypes 63, 47, 29 and 56 showed high resistance to anthracnose. There was no correlation between microsatellite markers and resistance to Colletotrichum spp., however moderate to high genetic diversity was observed. In the biocontrol test, the species T. virens and T. tomentosum showed the greatest potential antagonist to Colletotrichum spp. The results of this study contribute to the elucidation of the Colletotrichum spp. x pecan, as well as, provide subsidies for the development of future studies involving the improvement and control of anthracnose in the crop.